A Comparative Study On Pile Design Of Residential Buildings On Soft Soil Utilizing End-Bearing Pile Vs. Friction Pile - Lee, Yew Xu; Ling, Felix Ngee Leh (Recent Trends in Civil Engineering and Built Environment, 2021)
Pile foundation was most commonly used for structure built on soft soil and failure such as settlement always been noticed after installation and when subjected to building load. Hence, it is important to study the effect of embedded pile length and load transfer mechanism on pile settlement due to drving force and building load. Both numerical and calculation analysis was carried out by Plaxis 2D 2019 and published formula respectively. A published simulation model was utilized as base model while parametric studies were conducted with proposed pile in different embedded length installed in clay deposit while subjected to simulated driving force and building load. The results of the research showed that pile settlement induced by driving force was found to be decreased with increment of embedded pile length while pile settlement due to static building load had found to be decreased with increment of embedded pile length until an optimum length, in which settlement of pile was increased beyond its optimum length. In this research, friction pile was found to be a better option as compared to end bearing pile. It is recommended that field research should be carried out to obtaine a more reliable result.